PENGARUH KUALITAS SDM DAN PENERAPAN SISTEM AKUNTANSI SAK EMKM TERHADAP PENYUSUNAN LAPORAN KEUANGAN UMKM DI KECAMATAN GEMPOL - Soviatur Rochmah; Hermi Sularsih; As'adi As'adi (Unitri Press, 2021)
The purpose of this study was to determine the effect of the quality of human resources and the application of the SAK EMKM accounting system on the preparation of MSME financial reports in Gempol sub-district. Causality research with survey method is used as this research method. The owners of MSMEs registered with the Pasuruan Regency Cooperatives and MSMEs are the research population. The method of determining the sample that has been using was Purposive Sampling method with several criteria. Respondents in this study were 98 MSME owners. Data collection techniques using a questionnaire. The data analysis technique used multiple linear regression analysis. The research findings were the quality of human resources, and the application of the SAK EMKM accounting system has an effect on the preparation of MSME financial reports in Gempol District because competence is needed to present quality reports.